Transfronterizo Children's Literacies of Surveillance and the Cultural Production of Border Crossing Identities on the U.S.–Mexico Border. (30th December 2020) - Nuñez, Idalia; Urrieta, Luis
Abstract : This article examines the cultural production of three transfronterizo children who daily, physically cross a U.S.–Mexico international bridge. Drawing on theories of identity, border inspections, literacy, and language, the findings reveal that transfronterizo children developed literacies of surveillance, or the acquired and produced language and literacy practices to move across the surveillance, inspectors, and border. Transfronterizo children strategically used their full linguistic repertories to legitimize their border crossing identities in the context of surveillance.